Effect and Mechanism of Soluble Starch on Bovine Serum Albumin Cold-Set Gel Induced by Microbial Transglutaminase: A Significantly Improved Carrier for Active Substances - Shi, Haoting; Ding, Changsheng; Yuan, Jianglan (Foods, 2023)
Soluble starch (SS) could significantly accelerate the process of bovine serum albumin (BSA) cold-set gelation by glucono-δ-lactone (GDL) and microbial transglutaminase (MTGase) coupling inducers, and enhance the mechanical properties. Hardness, WHC, loss modulus (G″) and storage modulus (G′) of the gel increased significantly, along with the addition of SS, and gelation time was also shortened from 41 min (SS free) to 9 min (containing 4.0% SS); the microstructure also became more and more dense. The results from FTIR, fluorescence quenching and circular dichroism (CD) suggested that SS could bind to BSA to form their composites, and the hydrogen bond was probably the dominant force. Moreover, the ability of SS to bind the original free water in BSA gel was relatively strong, thereby indirectly increasing the concentration of BSA and improving the texture properties of the gel. The acceleration of gelling could also be attributed to the fact that SS reduced the negative charge of BSA aggregates and further promoted the rapid formation of the gel. The embedding efficiency (EE) of quercetin in BSA-SS cold-set gel increased from 68.3% (SS free) to 87.45% (containing 4.0% SS), and a controlled-released effect was detected by simulated gastrointestinal digestion tests. The work could put forward new insights into protein gelation accelerated by polysaccharide, and provide a candidate for the structural design of new products in the food and pharmaceutical fields.